What are the risk factors of injury for a rowing athlete? - Park, K. J. (The Journal of Sports Medicine and Physical Fitness, 2024)
BACKGROUND: The aim of this study was to examine the specific characteristics of injuries (injury location, injury type, and time to return to sports) based on sex and rowing style. METHODS: We included 60 adolescent rowers (Sweep male and female, 12 respectively; Sculling male and female, 18 respectively) who underwent training in Korea from January to December 2023. Sports injuries were meticulously recorded using the Daily Injury Report form issued by the International Olympic Committee for rowers characteristics (sex, rowing style) and injury characteristics (injury location, injury type). The injury incidence rate (IIR) per 1000 h of training was calculated using the 95% Poisson Confidence Interval. A ?2 test was performed to compare the characteristics of the rowers and injury characteristics. RESULTS: The overall IIR was 4.25 injuries per 1000 training hours. The IIR was lower for men than for women (P<0.001). However, sweep and sculling were similar (P=0.269). There was a difference in the affected body regions according to the sex and rowing style (P=0.028, P=0.005; respectively). Time to return to sports varied between rowing styles (P=0.049) and sexes (P=0.033), and it also differed in sweep (P=0.002) and sculling (P=0.045) depending on body regions. CONCLUSIONS: These results should be incorporated into programs that are aimed at improving the performance of these rowers and preventing sports injuries. In addition, can be used as data to determine their return to sport.